ACADEMIC STRESS AND EMOTIONAL INTELLIGENCE IN DENTAL STUDENTS OF A PERUVIAN UNIVERSITY - Picasso Pozo, Miguel Angel (2016)
Objective: To determine the level of academic stress and Emotional Intelligence (IE), and the relationship between both variables in dental students. Material and methods: An observational, descriptive and cross-sectional study was performed. The sample consisted of 82 students of V cycle of the San Martin de Porres University. Academic stress was measured by the Inventory SISCO, and EI by the TMMS-24 instrument. The relationship between variables was determined by ANOVA and Kruskal-Wallis tests. Results: 93.9% of students reported having presented stressing times during the course of the semester. Most of the responders presented a deficient perception of his emotions (71,9 %), whereas 41,5 % and 28 % should improve the understanding and regulation of their emotions, respectively. By analyzing the relationship between the frequency of the stressor agents, symptoms associated with stress and strategies of confrontation with the dimensions of EI, only relationship between symptoms and u